P458 Low adherence to Mediterranean diet is associated with increased adipose tissue in patients with ulcerative colitis (UC) after pouch surgery: a cross sectional study. (30th January 2023) - Pfeffer-Gik, T; Godny, L; Ollech, J; Wasserberg, N; White, I; Cohen, S; Broitman, Y; Avni-Biron, I; Banai, H; Snir, Y; Yanai, H; Yackobovich Gavan, M; et al.
Abstract: Background: Obesity [body mass index (BMI) ≥30 kg/m 2 ] prevalence in patients with inflammatory bowel diseases (IBD) ranges between 15-40%. Dual-energy x-ray absorptiometry (DEXA) is the gold standard for body composition evaluation. Patients with ulcerative colitis (UC) who undergo total proctocolectomy and pouch surgery may develop small bowel inflammation (pouchitis) resembling Crohn's disease (CD). We aimed to assess body composition of patients with UC-pouch and potential risk factors for high adiposity. Methods: Patients with UC-pouch ages 18-50 were recruited. Adipose tissue was assessed by DEXA (increased adipose tissue defined as > 26% male, >31% female), sarcopenia- assessed by hand-grip (defined as <30 kg male, <20 kg female). Clinical data, biochemical and inflammatory markers documented, Mediterranean diet adherence assessed by the Israeli Mediterranean diet (I-MEDAS) questionnaire. Results: Recruited patients: 30: male/female 14/16; median age 45 (IQR 31-51.7) years; median BMI 23.2 (IQR 21-26.5); median pouch age 17 (IQR 10-25) years. One patient was obese (BMI ≥ 30 kg/m 2 ) and seven-overweight (BMI 25-29.9 kg/m 2 ). Median fat percentage 34.7 (IQR 30.1-39.7); 23/30 (76.6%) had increased adipose tissue. 14/30 (46%) patients were defined as normal weight obesity- normal BMI with increased adipose tissue. In univariate analysis comparing males to females, age and I-MEDAS score were comparable. Females were less physically active (p=0.028), had lower BMI (p=0.043), and higher rates of elevated adipose tissue (p=0.002). In multivariate analysis adherence to the Mediterranean diet was associated with lower adipose tissue regardless of sex and BMI (p<0.001). Sarcopenia was found in 1 (3.33%) female patient. Conclusion: Patients with UC-pouch are at risk for "Normal-weight obesity", an uprising health concern, having increased adipose tissue regardless of BMI and sarcopenia. Adherence to the Mediterranean diet is inversely associated with increased adiposity, and may be used to modify adiposity in patients with UC after pouch surgery, irrespectively of BMI.